Increasing the reliability of the equipment of oil and gas transportation industry due to polymeric nanocomposites - O.M. Bezbach, S.V. Voronenko, A.V. Buketov, M.Yu. Amelin R.Yu. Negrutsa, A.V. Sapronova (JOURNAL OF HYDROCARBON POWER ENGINEERING, 2018)
On the basis of the performed tests of the thermophysical properties of epoxy composites filled with nanoparticles, using modern research methods, the permissible temperature ranges have been set, at which it is possible to use the developed materials. The thermal coefficient of linear expansion (α) and heat resistance (Т) of epoxy composites have been investigated. The absolute values of the thermal coefficient of linear expansion of materials, which can be used in different temperature ranges, have been defined. It has been proved that for the formation of composite materials with enhanced thermophysical properties, it is advisable to use a nano filler in the amount of q = 0.5 %. This material is characterized by the highest activation energy, resistance to structural change at the highest temperatures and intense interaction of functional groups of the filler and epoxy oligomer during the formation at the molecular level among all investigated materials.